Model design for factors affecting the packaging of Iranian fruit and vegetables for export. (12th July 2022) - Faraghian, Hamid; Dolatabadi, Hossein Rezaie; Esmaelian, Majid
Packaging is one of the most substantial and determinative processes of goods consumption and supply, which can be a competitive advantage in comparison with rivals. Foodstuff packaging ensures that export products are sent to the considered destination without any problem. Moreover, proper packaging of goods and customer satisfaction would boost the sale rate in target markets. This study aimed at designing a model for factors affecting the packaging of agricultural products for export. In order to present a new and comprehensive research in the export and packaging field, qualitative method and qualitative content analysis approach were used. In qualitative content analysis method, experts in the field of packaging and export, businessmen, and top managers of companies that work in fruits and vegetables export were interviewed to identify factors affecting export agricultural goods packaging. Variables were identified by using theme analysis method through MAXQDA Software. The obtained results indicated that factors affecting the packaging include seven categories: environmental factors, physical characteristics, shipping terms, rules and regulations, export destination features, product information, and product type.